PENGEMBANGAN MEDIA PEMBELAJARAN âKUTEBAKâ MATA PELAJARAN DASAR-DASAR PERBANKAN KELAS X AKUNTANSI SMK NEGERI 3 SURAKARTA - Oktaviana, Charisma Nur; Santoso, Sigit; Sumaryati, Sri (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objectives of this research are to investigate Â the feasibility of the KUTEBAK learning media in the Banking Basics subject matter learning. The target of this research was all of the students in Grade X of Accounting Expertise Department of State Vocational High School 3 of Surakarta. This research used the research and Development (R&D) method with the ADDIE approach, which consisted of several phases, namely: analysis, design, development, implementation, and evaluation. The data of research were collected through in-depth interview and questionnaire and were analyzed by using the descriptive quantitative analysis and the descriptive qualitative analysis. The results of the research are as follows. The developed âKUTEBAKâ educational games is very feasible to be used in the Banking Basics subject matter learning as indicated by the results of the learning media expert with the score of 85.50% (very feasible), of the learning material expert with the score of 80% (feasible), and of the practitioner with the score of 89.63% (very feasible). The score of the individual testing was 81.76% (very feasible); the score of the small group testing was 81.76%; and the score of the field testing was 80.18% (feasible). Keywords: KUTEBAK, learning media, learning interest, educational games.Â Â Â  Â ABSTRAKPenelitian ini bertujuan untuk mengetahui: kelayakan media pembelajaran KUTEBAK dalam pembelajaran Dasar-Dasar Perbankan. Sasaran dalam penelitian ini adalah seluruh siswa Kelas X Bidang Keahlian Akuntansi di SMK Negeri 3 Surakarta. Penelitian ini merupakan penelitian pengembangan dengan metode ADDIE yang terdiri dari tahap analysis, design, development, implementation, dan evaluation. Pengumpulan data dilaksanakan dengan teknik wawancara dan teknik angket. Analisis data menggunakan analisis deskriptif kuantitatif dan deskriptif kualitatif. Hasil penelitian adalah sebagai berikut ini. Permainan Edukasi KUTEBAK yang dikembangkan sangat layak untuk digunakan pada mata pelajaran Dasar-Dasar Perbankan. Berdasarkan penilaian ahli media diperoleh skor 87,50% (Sangat Layak), ahli materi dengan skor 80% (Layak), ahli praktisi dengan skor 89,63% (Sangat Layak). Uji coba perorangan dengan skor 84,71% (Sangat Layak), uji coba kelompok kecil dengan skor 81,76% (Sangat Layak), uji coba lapangan dengan skor 80,18% (Layak).Kata Kunci : KUTEBAK, media pembelajaran, minat belajar, permainan edukasi